Perancangan Sistem Informasi Akuntansi RAB Pemeliharaan Peralatan Dengan Microsoft Visual Studio 2010 Dan Database MySQL: Studi Deskriptif Pada Dinas ATR/BPN Kota Bandung - Jimmi Lumbantobing; Perwito Perwito; Ratnanto Aditiarno (Program Studi Magister Manajemen, Institut Manajemen Koperasi Indonesia, 2023)
The Budget Plan is one of the attributes in knowing the amount of the Budget for one accounting period. In the Realization process, the use of Planned Budget funds must be controlled continuously so that it is in accordance with what is expected when preparing the Budget Plan. Recording of the Budget Plan that is incorporated into the general accounting system will cause data discrepancies and must be revised repeatedly. A separate system with capabilities equivalent to the main system will greatly assist in processing the Budget Plan data. In this study, using MS. Visual Studio 2010 and MySQL Database as a system design tool. Based on the trial results of MS. Visual Studio 2010 is able to design a system according to the proposal, this shows that the system has worked well as expected.